Search for Scalar Diphoton Resonances in the Mass Range 65−600 GeV with the ATLAS Detector in pp Collision Data at s√ = 8 TeV - Onofre, A. (2014)
A search for scalar particles decaying via narrow resonances into two photons in the mass range 65–600 GeV is performed using 20.3 fb−1 of ffiffiffi s p ¼ 8 TeV pp collision data collected with the ATLAS detector at the Large Hadron Collider. The recently discovered Higgs boson is treated as a background. No significant evidence for an additional signal is observed. The results are presented as limits at the 95% confidence level on the production cross section of a scalar boson times branching ratio into two photons, in a fiducial volume where the reconstruction efficiency is approximately independent of the event topology. The upper limits set extend over a considerably wider mass range than previous searches.